STUDY OF DRUG-DRUG INTERACTION IN THE INPATIENTS OF A TERTIARY CARE HOSPITAL AT CALICUT - George, Greeshma K; Sundaran, Siraj; Cp, Ashar Ali; Km, Mubeena; Ph, Thansiya; G, Babu; Gopalakrishnan, Arun (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The study was conducted to monitor the potential drug-drug interactions in the prescriptions of inpatients in a tertiary care hospital based on the mechanism and severity. Methods: This prospective observational study was conducted by collecting the prescriptions containing two or more drugs. The interactions were checked using an interaction checker and were categorized into pharmacokinetic and pharmacodynamic interactions on the basis of mechanism of action and severity based on the risks or consequences of the interactions. Result: Among 150 randomly collected prescriptions, 123 (82%) prescriptions had 396 drug-drug interactions. The pharmacodynamic drug interactions (77.27%) were more common when compared to pharmacokinetic drug interactions (22.73%). There was high prevalence of drug-drug interactions among the patients above the age of 60 years (56.09%). The moderate drug-drug interactions (81.81%) were found to be more when compared to the major (10.61%) and minor (7.58%) interactions. The neurology department prescriptions were observed to have more number of drug-drug interactions (26.01%). Conclusion: A systematic approach and close monitoring of the medication chart is necessary to identify the potential drug-drug interactions. The clinicians and other health-care professionals at the study site require an awareness program in regard to identification and management of drug-drug interactions. Clinical pharmacist can play an important role in the monitoring and management of drug-drug interactions.